2018
DOI: 10.1002/iub.1758
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase reverse transcriptase suppression inhibits cell proliferation and promotes cell apoptosis in hepatocellular cancer

Abstract: We aimed to investigate the role of telomerase reverse transcriptase (TERT) in hepatocellular cancer (HCC) cells. R software was used for differential expressed gene analysis. Western blot and quantitative real time polymerase chain reaction (qRT-PCR), respectively, were used to detect protein expression and mRNA level of TERT in tumor cell lines. Real-time quantitative telomeric repeat amplification protocol assay, MTT assay, colony formation assay, and flow cytometry (FCM) assay were used to analyze the telo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
(28 reference statements)
1
7
0
Order By: Relevance
“…However, whether hTERT leads the cell cycle by inhibiting factors other than telomeres, including CDKN2A, has remained unknown. The current study demonstrated that hTERT expression is not limited to anti-apoptosis and tumor survival but also affects the tumor cell cycle [11,14]. We also confirmed that inhibition of hTERT induces apoptosis ( Figure S2).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…However, whether hTERT leads the cell cycle by inhibiting factors other than telomeres, including CDKN2A, has remained unknown. The current study demonstrated that hTERT expression is not limited to anti-apoptosis and tumor survival but also affects the tumor cell cycle [11,14]. We also confirmed that inhibition of hTERT induces apoptosis ( Figure S2).…”
Section: Discussionsupporting
confidence: 80%
“…Aging of natural cells through reduction of telomere causes apoptosis, or apoptosis also occurs through hTERT inhibition. Thus, over-expression of hTERT leads to the synthesis of telomeres to prevent apoptosis in most solid tumors [11]. However, whether hTERT leads the cell cycle by inhibiting factors other than telomeres, including CDKN2A, has remained unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[78] In cancer cells, hTERT is over-expressed to create telomeres as a mechanism to prevent apoptosis. [11,79] However, it is still unknown if hTERT inhibits other factors to reinforce the cell cycle. Choi et al hypothesized that if hTERT is somehow regulated, an anti-tumor strategy could be developed in HCC management by using human kruppel-related 3 and factors that are involved in the cell cycle of HCC cell lines.…”
Section: Using Hkr3 To Inhibit Htert In Hepatocellular Carcinoma Cellmentioning
confidence: 99%